Studies in Semitic Vocalisation and Reading Traditions - Hornkohl, Aaron D.; Khan, Geoffrey (Cambridge Semitic Languages and Cultures, 2020)
"This volume brings together papers relating to the pronunciation of Semitic languages and the representation of their pronunciation in written form. The papers focus on sources representative of a period that stretches from late antiquity until the Middle Ages. A large proportion of them concern reading traditions of Biblical Hebrew, especially the vocalisation notation systems used to represent them. Also discussed are orthography and the written representation of prosody. Beyond Biblical Hebrew, there are studies concerning Punic, Biblical Aramaic, Syriac, and Arabic, as well as post-biblical traditions of Hebrew such as piyyuṭ and medieval Hebrew poetry. There were many parallels and interactions between these various language traditions and the volume demonstrates that important insights can be gained from such a wide range of perspectives across different historical periods."